Caves of the Ferashih in Dhahra, Mostaganem - karamane, abdelkader (Journal of Social Sciences and Humanities, 2024)
The article focuses on one of the heinous crimes committed by French colonial in the caves of Al-Frachih in Dahra Mostaganem, from the seventeenth to the twentieth June 1845 AD. We mention in details the events of this massacre byextrapolating the different hitorical sources which are the writings of some foreign travelers, the reports of French leaders who lived through all stages and details, of the crime in addition to the international press’ writings that reacted to this historical event and effectively contributed to exposing the French occupation in the world, when this french colonial wanted Covering up the crime by obliterating the material evidence, it bitterly failed and the press succeeded in publishing its facts, all of these previous events led to a huge uproar in the international political and media arena. We also relied on collecting all kinds of material evidence from the archaeological site, the evidence of which is still preserved until now , we olso try to document it through the field study, which helped us describe the cave and its remained material evidence, as well as taking photographs as much as possible. It is olso one of our main goals that we want to achieve it through this research paper, with all transparency and scientific credibility.